2019
DOI: 10.1021/acs.iecr.9b01629
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Oil Production Using Silica-Based Nanofluids: Preparation, Stability, and Displacement Mechanisms

Abstract: A novel two-step preparation of a silica nanofluid (Si-NF) with potential for light oil recovery is herein presented. It was observed that a Si-NF, prepared by dispersing silica nanoparticles (Si-NPs) in poly­(vinyl alcohol) (1%) under carbon dioxide gas bubbling, is stable for 30 days at a temperature as high as 55 °C without any visible sedimentation. Unstable Si-NFs formed siliceous gels whose strength depends on Si-NP load. The spectral characterization revealed that prepared Si-NFs consisted of silanols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…During the sonication stage, the ultrasound waves, by stretching the molecular spacing of fluid, creates cavities within, which cause subsequently the chemical bonds to break [44]. However, due to the intrinsic properties of MO-NPs, a poor dispersion is often yielded which is mitigated by either extending the mixing time, adding few drops of acidifying agents [45] or even bubbling gas during the preparation [43].…”
Section: Preparation Using Two-step Methods Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…During the sonication stage, the ultrasound waves, by stretching the molecular spacing of fluid, creates cavities within, which cause subsequently the chemical bonds to break [44]. However, due to the intrinsic properties of MO-NPs, a poor dispersion is often yielded which is mitigated by either extending the mixing time, adding few drops of acidifying agents [45] or even bubbling gas during the preparation [43].…”
Section: Preparation Using Two-step Methods Approachmentioning
confidence: 99%
“…However, combing both the sonication and the magnetic stirring could prolong the stability of the nanofluid. Furthermore, Nguele et al [43] and later Ngo et al [47] reported that bubbling gas during the preparation could further enhance the stability regardless the type of base fluid (Figure 5).…”
Section: Enhancing the Stability Of Nanofluidmentioning
confidence: 95%
See 2 more Smart Citations
“…CO 2 gas was bubbled into the mixture to improve the stability of the nanofluid by the enhancement of the cavitation collapse, which proved to be good to obtain a more stable nanofluid. 21 …”
Section: Methodsmentioning
confidence: 99%